2013
DOI: 10.1111/pan.12197
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of spontaneous ventilation technique using dexmedetomidine for rigid bronchoscopic airway foreign body removal in children

Abstract: Dexmedetomidine may provide appropriately deep anesthesia and ideal conditions for rigid bronchoscopic airway foreign body removal without respiratory depression or hemodynamic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…[8,9] Furthermore, dexmedetomidine can provide appropriate anesthesia depth and ideal conditions for rigid bronchoscopic airway removal of foreign bodies in children. [10] However, there are no studies to date that have compared the sedative effects and adverse reactions of different sedatives during FFB in critically ill ICU patients on mechanical ventilation. In the present study, the clinical effectiveness of dexmedetomidine and midazolam for sedation of ICU patients before FFB was compared.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Furthermore, dexmedetomidine can provide appropriate anesthesia depth and ideal conditions for rigid bronchoscopic airway removal of foreign bodies in children. [10] However, there are no studies to date that have compared the sedative effects and adverse reactions of different sedatives during FFB in critically ill ICU patients on mechanical ventilation. In the present study, the clinical effectiveness of dexmedetomidine and midazolam for sedation of ICU patients before FFB was compared.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchospasm and hypoxemia are common complications during the TFB removal procedure and could delay surgical intervention . In the present study, we found that the incidences of bronchospasm and hypoxemia in the LE and LED groups were much lower than those in the C and S groups, indicating that dexamethasone with lidocaine and epinephrine could reduce the incidences of bronchospasm and hypoxemia .…”
Section: Discussionmentioning
confidence: 46%
“…Severe morbidity and death have been associated with chloral hydrate . Similar problems have not been identified with dexmedetomidine . Intranasal dexmedetomidine appears to be a safer and more acceptable method of sedating children than oral chloral hydrate .…”
Section: Discussionmentioning
confidence: 85%